2020
DOI: 10.1038/s41598-020-70865-7
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxic gene expression in chronic hepatitis B virus infected patients is not observed in state-of-the-art in vitro and mouse infection models

Abstract: Hepatitis B virus (HBV) is the leading cause of hepatocellular carcinoma (HCC) worldwide. The prolyl hydroxylase domain (PHD)-hypoxia inducible factor (HIF) pathway is a key mammalian oxygen sensing pathway and is frequently perturbed by pathological states including infection and inflammation. We discovered a significant upregulation of hypoxia regulated gene transcripts in patients with chronic hepatitis B (CHB) in the absence of liver cirrhosis. We used state-of-the-art in vitro and in vivo HBV infection mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
(121 reference statements)
3
14
0
Order By: Relevance
“…To understand whether HIF-2α transcriptional activity dominates in the HBV-infected liver we investigated the relative contribution of HIF-1α or HIF-2α activity in CHB biopsy samples. 21 38 of the hypoxia genes showing increased expression in CHB were defined as HIF-1α (n = 26), HIF-2α (n = 11) or co-regulated (n = 1) genes, 33 showing clear evidence for both HIF-1α and HIF-2α transcriptional activity in vivo . These data show the complexities of studying viral and host transcriptional responses to low oxygen in PHHs ex vivo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To understand whether HIF-2α transcriptional activity dominates in the HBV-infected liver we investigated the relative contribution of HIF-1α or HIF-2α activity in CHB biopsy samples. 21 38 of the hypoxia genes showing increased expression in CHB were defined as HIF-1α (n = 26), HIF-2α (n = 11) or co-regulated (n = 1) genes, 33 showing clear evidence for both HIF-1α and HIF-2α transcriptional activity in vivo . These data show the complexities of studying viral and host transcriptional responses to low oxygen in PHHs ex vivo.…”
Section: Resultsmentioning
confidence: 99%
“…HBV integrants are thought to be the major source of HBsAg expression in chronic disease that have been associated with exhausted antiviral T cell responses. 1 , 50 Our observation that integrant encoded preS1/S transcripts are oxygen-insensitive is relevant if one considers the hypoxic nature of the HCC environment 21 , 51 and how this could influence HBsAg expression, a biomarker for monitoring patients’ response to new therapies. 52 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PacBio circular consensus sequencing reads analysed in this study have been previously published and can be found in the European Nucleotide Archive (PRJEB12450) [1]. The RNA-seq libraries of hepatitis B virus (HBV)-positive biopsy samples of human liver tumours and tissues, and portal vein tumour thrombosis (129, 182 and 92 libraries, respectively), and HBV-infected primary human hepatocytes (83 libraries) and human cultured cells HepaRG (4 libraries) and HepG2-NTCP (11 libraries) were downloaded from the Sequence Read Archive [2–18] (see the metadata in Table S1, available with the online version of this article).…”
Section: Data Summarymentioning
confidence: 99%